KEPENTINGAN PARLEMEN EROPA MENGELUARKAN RESOLUSI NO. 2952 (RSP) TERHADAP QATAR DALAM KASUS EKSPOLITASI BURUH IMIGRAN INDIA TAHUN 2013 - Efryli Derta; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is intended to explain the reason for the European Parliament passed a resolution no. 2952 (RSP) in the case of immigrant workers India in 2013. Candidate to host the 2022 FIFA World Cup bebeneficial for Qatar because, Qatar intends to change the perception of the international community through sport and tourism. Qatar has built several stadiums in Doha with the quantity of capital of US$ (US dollars) to 200 billion for new infrastructure in 2011, US$ 34Billionforrailroad facilitiesandmetrosystems, US$ 7Billionforthe portas well as forBusiness and Commerce amount of US$ 4 billionin the same year. Quantity capital cost of infrastructure resulted in the Government of Qatar over whelme dregulate labor costs of some countries such as Pakistan, India, Nepal, SriLanka, Egypt, Philippines, and even Indonesia. Immigrant workers are not given a salary according to the job for 12 hours to build a stadium or other infrastructure in Qatar. Criticism from politician sand groups,human rights defenders make the EuropeanParliament issued a resolution calling for the Government of Qatar to stop the enslavement of the Indian labor by providing for each worker.European Parliament urged the government of Qatar to revoke Kafala system, which employs the workers employment by giving the entire identity to the guarantor.Key words : Constructivism, European Parliament, kafala, migrant workers, Qatar.